The Application Status of Chinese Herbal Medicine in Military Health Service in China - 杨葛亮 顾伟 张慧卿 翟笑枫 李霄茜 凌昌全 (Chinese journal of integrative medicine, 2016)
Military medicine has had a long history in China since the emergence of the war. Chinese medicine, especially Chinese herbs, was widely used in China as well as other Asian countries for the prevention and treatment of diseases in the military for hundreds of years. However, the use of Chinese medicine in military health service has never been well studied. In this article, we bdefly summarize the application status of Chinese herbal medicine in military health service in China, putting particular emphasis on special military environment, in an attempt to build a bridge between Chinese medicine and military health service and promote the quality of health service for the military and maintain wodd Deace.